Abortion Law awareness and Abortion Services Utilization among reproductive age women of Inarwa municipality of Eastern Nepal - Khanal, Vijay Kumar; Ghimire, Hari Prasad; Bhattachan, Meika; Nepal, Gyanu; Budhathoki, Shyam Sundar; Sharma, Khem Raj; Gupta, Pramendra Prasad; Pokhrel, Paras Kumar (Journal of Gandaki Medical College-Nepal, 2020)
Introduction: Globally, reproductive health and quality of life among female population has been found to be unsatisfactory in developing world. Until 1963, Nepal’s 1854 legal code known as MulukiAin was revised numerous times that banned abortion exempting risk of women’s life. Enactment of New Abortion Policy from 2003 brought landmark reforms to the women’s choice in family planning methods and ended the sufferings of lengthy prison sentences for abortion crimes. This study was conducted to explore the level of awareness about abortion law with regard to health care utilization among women of reproductive age group along with its association with socio-demographic characteristics. Methodology: A cross-sectional study was conducted in March 2014, in Inarwa Municipality among women of reproductive age group (16 to 49 years). Convenient sampling was done to collect data from households. Data was entered and analyzed in SPSS 11.5 and presented in tabular form. Chi-square test was used to show association of awareness of abortion law and socio-demographic variables. Results: education, age at first marriage and age at 1st pregnancy was found to be significant (p value: <0.005). Conclusion: As media was the most used source of information, more education on awareness of abortion law and health care utilization should be disseminated through this medium.